Improved tribological and thermo‐mechanical properties of epoxy resin with micro‐nano structured ZrO2/Ti3C2 particles. Issue 41 (29th May 2021) - Yi, Jie; Yang, Yaru; Zhang, Yalin; Cao, Miao; Wang, Tianle; Guan, Jipeng; Xiao, Yunchao; Zhang, Yuanjie; Tang, Bolin; Shen, Xiaojun
Abstract: Inherent brittleness and poor wear resistance of epoxy resin severely restricts its practical application in many applications. In this present, a micro‐nano structured ZrO2 /Ti3 C2 particle was employed to improve the tribological and thermo‐mechanical properties of epoxy resin. The micro‐nano structured ZrO2 /Ti3 C2 particles are synthesized by hydrothermal growth of nano‐ZrO2 onto the surface of accordion‐like Ti3 C2, and the ZrO2 /Ti3 C2 /epoxy composites are fabricated by solution blending and curing reaction. The surface morphology of ZrO2 /Ti3 C2 particles and the fracture surface of ZrO2 /Ti3 C2 /epoxy composites were investigated. Test results indicated that the wear rate, storage modulus and glass transition temperature of epoxy resin is effectively improved by incorporation of ZrO2 /Ti3 C2 particles, maybe ascribing to the strong interfacial interaction between micro‐nano structured ZrO2 /Ti3 C2 and epoxy matrix. In addition, the wear mechanism of ZrO2 /Ti3 C2 /epoxy composites were further revealed by analyzing their worn surfaces and wear debris. This work provides a promising strategy for improving the tribological and thermo‐mechanical properties of epoxy. Abstract : The micro‐nano structured ZrO2 /Ti3 C2 particles are synthesized by hydrothermal growth of ZrO2 nanoparticles onto the surface of accordion‐like Ti3 C2, and the ZrO2 /Ti3 C2 /epoxy composites were fabricated by solution blending and curing reaction. The incorporation of ZrO2 /Ti3 C2 greatly improved the wear rate of epoxy resin, and simultaneously enhanced the storage modulus and glass transition temperature of epoxy resin.